Characterization of lectinlike surface components on Capnocytophaga ochracea ATCC 33596 that mediate coaggregation with gram-positive oral bacteria. - Weiss, E I (1987)
The interactions between Capnocytophaga ochracea ATCC 33596 and Streptococcus sanguis H1, Actinomyces naeslundii PK984, or Actinomyces israelii PK16 are dependent on specific recognitions between heat-sensitive adhesins on C. ochracea and heat-stable structures (probably carbohydrate-containing receptors) on the surfaces of these gram-positive coaggregation partners. The coaggregation of C. ochracea with each of these three organisms was inhibited by L-rhamnose and D-fucose and to a lesser extent by beta-methyl-galactoside. The reaction with S. sanguis was the most sensitive, while the coaggregation with A. israelii was the least sensitive and was only partially inhibited by each of the sugars that were considered to be effective inhibitors. A more effective inhibition of the coaggregation between C. ochracea and A. israelii was achieved by adding a combination of the 6-deoxysugars and N-acetylneuraminic acid. To further characterize the coaggregations, naturally occurring coaggregation-defective (Cog-) mutants of C. ochracea were obtained from several different selections. Three phenotypically distinct groups of mutants were were isolated. Type 1 mutants failed to coaggregate with S. sanguis only. Type 2 mutants lost ability to interact with both S. sanguis and A. naeslundii. Type 3 mutants failed to coaggregate with all three coaggregation partners. Characterization of the Cog- mutants by sugar inhibition studies made it possible to distinguish three classes of adhesin activity.